(untitled) (Web of Teachers: Inderscience Research, 2024)
Particular attention is paid to soil, which is considered the main tool in the system of all countries for the conservation, restoration and enhancement of its productivity. In this regard, a number of regulatory documents are adopted in our country, the main purpose of which is to protect the soil, which is the main means of production.